Resolving the Judgment and Decision-Making Paradox Between Adaptive Learning and Escalation of Commitment - Wong, Kin Fai Ellick; Kwong, Jessica Y. Y. (Management Science, 2018)
A paradox in organizational research on judgment and decision making is that although the law-of-effect in adaptive learning suggests that people’s tendency to take a decision decreases after the decision receives negative consequences, people often exhibit an opposite action pattern of escalation of commitment. To address this paradox, this paper proposes that the unit of law-of-effect can be extended from a decision level to a strategy level (i.e., a group of planned decisions). A strategy organizes decisions from being consistent with the law-of-effect in one extreme to being consistent with escalation of commitment in another extreme. This paper shows that the favorability of the law-of-effect strategy (versus the escalation strategy) is likely to be underestimated at the beginning of a learning process. This underestimation stabilizes over time because negative consequences decrease the likelihood of choosing the law-of-effect strategy in the future. Accordingly, escalation strategy will be preferred more in the learning process, thereby developing a pattern of behaviors that is contradictory to the law-of-effect at the decision level but consistent with the law-of-effect at the strategy level. This learning pattern was demonstrated in three simulations with different combinations that were specified to capture different aspects of escalation of commitment. This learning perspective offers a novel explanation of escalation, suggesting that escalation may occur without distorted motivation or cognition. Data and the supplementary material are available at https://doi.org/10.1287/mnsc.2016.2686 . This paper was accepted by Yuval Rottenstreich, judgment and decision making.